ANALISIS KEBUTUHAN PENGEMBANGAN POSTER DIGITAL GLOSARIUM BAHASA LATIN MORFOLOGI TUMBUHAN SEBAGAI MEDIA PEMBELAJARAN BERBASIS CANVA - Angel Masing, Feliksitas; Yasinta Moi, Maria; Felisima Tae, Lidwina (Universitas Cokroaminoto Palopo, 2024)
This study aims to: 1) determine the process and obstacles faced by lecturers and students in learning plant morphology courses; 2) find out information on the use of learning media in plant morphology courses; 3) develop canva-based learning media in plant morphology courses. The subjects of this study were lecturers teaching plant morphology courses and semester III students of the Biology Education Study Program, Timor University. Data collection techniques were in the form of observation guidelines, interviews and documentation. The data analysis technique used was qualitative descriptive analysis. The results of the study showed that: 1) The process of learning plant morphology has been going well but there are still obstacles faced, namely difficulties in learning the Latin language of plant parts; 2) the learning media that have been used so far are print media, audio media, audio-visual media, but canva-based audio-visual media has never been used; 3) based on the results of the needs analysis, it is necessary to develop canva-based learning media in the form of a digital poster of a Latin glossary of plant morphology.